Radiology of Positioning and Applied Anatomy (For Students and Practitioners) - Garkal GS; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2000)
The radiographic examination of human body is very complex and different views like anteroposterior, oblique, lateral etc., are required for proper diagnosis of pathology and functioning of the affected part. Different body parts require different positioning and views, the patient has to acquire various positions as some are demonstrated while the person is standing while some require the person to be in sitting position to lie down in required position and care to be taken while positioning the patient to avoid radiological artifacts which may lead to false results or may cause further trauma to the patient apart from these the exposure settings should be set accordingly to avoid high exposure to harmful X-rays,improper exposure leads to decreased contrast which makes the interpretation difficult. The skull, upper extremities, lower extremities, chest, abdomen all require different exposure settings, position and views. Apart from these there are several Common Radiological Investigations which are done to soft tissues which requires in many cases contrast to give opaqueness to the part for visualization of different parts for diagnosis pathology and the proper functioning of the affected part. The radiological investigation requires a lot of practice and proper knowledge of anatomy and physiology of body for proper interpretation.
Keywords: Radiology and Nuclear Medicine; Electronic books